Protection for Free? : The Political Economy of U.S. Tariff suspensions - Mishra, Prachi (IMF Working Papers; Working Paper ;, 2010)
This paper studies the political influence of individual firms on Congressional decisions to suspend tariffs on U.S. imports of intermediate goods. We develop a model in which firms influence the government by transmitting information about the value of protection, via costless messages (cheap-talk) and costly messages (lobbying). We estimate our model using firm-level data on tariff suspension bills and lobbying expenditures from 1999-2006, and find that indeed verbal opposition by import-competing firms, with no lobbying, significantly reduces the probability of a suspension being granted. In addition, lobbying expenditures by proponent and opponent firms sway this probability in opposite directions.